Fetal heart rate and motor development in overweight and obese pregnant women. Issue 1 (April 2016) - Voegtline, Kristin M.; Costigan, Kathleen A.; Henderson, Janice L.; DiPietro, Janet A.
Abstract: Objective: To determine the relationship between maternal prepregnancy body mass index (BMI) and fetal cardiac and motor activity and integration during the second half of pregnancy. Methods: Longitudinal data were collected from 610 nonsmoking women with normally progressing pregnancies at three gestational periods (24, 30–32, and 36 weeks) across eight cohorts studied between 1997 and 2013. Fifty minutes of fetal heart rate and motor activity data were collected at each period via actocardiography in a laboratory setting. Data were digitized and analyzed using customized software. Standard BMI categories were computed from maternal prepregnancy weight and height. Participants were stratified into normal weight (n = 401, 65.7%), overweight (n = 137, 22.5%), or obese (n = 72, 11.8%). Results: Fetuses of obese women showed lower heart rate variability and fewer accelerations relative to fetuses of normal weight women. Fetuses of both obese and overweight women exhibited more vigorous motor activity than fetuses of normal weight women. Cardiac–somatic integration was reduced in both obese and overweight groups. Findings differed by gestational age at assessment. Conclusions: Excess maternal prepregnancy weight in overweight and obese women alters the normal trajectory of fetal cardiac and motor development and their integration, with effects amplified as pregnancy progresses.